More than meets the eye: The evolving phenotype of Weill–Marchesani syndrome—diagnostic confusion with geleophysic dysplasia. Issue 12 (16th August 2013) - Pimienta, Allen L.; Wilcox, William R.; Reinstein, Eyal
Abstract: The criteria for diagnosing and distinguishing between Weill–Marchesani syndrome (WMS) and geleophysic dysplasia (GD) are inexact and often overlap. We report the clinical findings and evolving phenotype for a period of 18 years in a patient whose diagnosis, and distinguishing characteristics, transformed from GD to WMS. Molecular testing demonstrated novel mutations in the ADAMTS10 gene confirming a diagnosis of autosomal recessive WMS in the proposita. We further report on phenotypic features not classically linked to WMS. These findings indicate that the Weill–Marchesani phenotype may be developed and is not always apparent in early childhood. © 2013 Wiley Periodicals, Inc.